2015
DOI: 10.1371/journal.pone.0132088
|View full text |Cite
|
Sign up to set email alerts
|

Gene Transcriptional and Metabolic Profile Changes in Mimetic Aging Mice Induced by D-Galactose

Abstract: D-galactose injection has been shown to induce many changes in mice that represent accelerated aging. This mouse model has been widely used for pharmacological studies of anti-aging agents. The underlying mechanism of D-galactose induced aging remains unclear, however, it appears to relate to glucose and 1ipid metabolic disorders. Currently, there has yet to be a study that focuses on investigating gene expression changes in D-galactose aging mice. In this study, integrated analysis of gas chromatography/mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 63 publications
(72 reference statements)
5
50
0
Order By: Relevance
“…Recently, studies focused on the roles of galactose in cellular senescence have shown that the mechanisms underlying d -gal -induced aging likely involve glucose and 1ipid metabolic disorders, increased oxidative damage, the accumulation of advanced glycation end products, impaired elimination of abnormal substances, accelerated cell apoptosis, and enhanced insulin resistance 22,24. The effects produced by d -gal differ with dosage (varying between 50 and 1,250 mg/kg/d), age group (varying between 6 weeks and 6 months), and time interval (varying between 6 and 10 weeks) 12.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies focused on the roles of galactose in cellular senescence have shown that the mechanisms underlying d -gal -induced aging likely involve glucose and 1ipid metabolic disorders, increased oxidative damage, the accumulation of advanced glycation end products, impaired elimination of abnormal substances, accelerated cell apoptosis, and enhanced insulin resistance 22,24. The effects produced by d -gal differ with dosage (varying between 50 and 1,250 mg/kg/d), age group (varying between 6 weeks and 6 months), and time interval (varying between 6 and 10 weeks) 12.…”
Section: Discussionmentioning
confidence: 99%
“…Galactose treatment was reported to cause increases in lipid peroxides and PC levels and decreases in antioxidant enzyme activities in serum and tissues like liver and brain, together with histopathological changes and progressive deterioration in learning and memory capacity in rodents (Aydın et al., ; Han, Lin, Lee, Liang, & Hou, ; Kalaz et al., ; Xiong et al., ). In addition, some investigators have detected that AGE levels were increased in serum, liver and brain tissues of GAL‐treated rats (Han et al., ; Song et al., ; Xiong et al., ; Zhou et al., ). However, studies investigating the effect of GAL‐induced accelerated ageing on male reproductive organs are quite limited.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidences indicate that increased reactive oxygen species (ROS) generation is associated with abnormal metabolism such as glucose autoxidation and result in the upregulation of transforming growth factor (TGF)‐β1, extracellular matrix (ECM) which implicated in the progression of cardiac fibrosis . D‐galactose (D‐gal) is a reducing sugar which is most commonly used to study aging‐ related pathological complications . Evidences from various studies suggest that D‐gal produces ROS during its metabolism in vivo and produced advanced glycation end‐products (AGEs) which eventually accelerate the aging process .…”
Section: Introductionmentioning
confidence: 99%